Merespons Hoaks dan Disinformasi: Literasi Digital sebagai Bagian dari Amar Ma’ruf Nahi Munkar - Najamudin Najamudin; Dwi Muliati; Anggun Duwi Wahyu Ziliwu; Feti Oktaviani; Mutiara Al-Nizar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid spread of hoaxes and disinformation in the digital era poses serious challenges to social cohesion, societal stability, and the internalization of moral values, particularly within Muslim communities. The circulation of unverified information has the potential to trigger conflict, polarization, and a decline in public trust. This study aims to explore digital literacy as an ethical and religious instrument in actualizing the Islamic principle of amar ma’ruf nahi munkar in the contemporary digital sphere. Employing a qualitative library research approach, the study examines classical Islamic sources, including the Qur’an and Hadith, alongside contemporary literature on digital communication ethics and digital citizenship. The findings indicate that digital literacy from an Islamic perspective extends beyond technical competence in accessing and disseminating information; it represents a form of moral responsibility (amanah) grounded in honesty (ash-shidq), prudence, and accountability. Practices such as information verification (tabayyun), clarification, and corrective engagement in online spaces are concrete expressions of amar ma’ruf nahi munkar. Strengthening ethically grounded digital literacy is therefore essential for fostering a healthy, just, and civilized digital public sphere.